Pedagogical brokering for STEM integration: Beyond partnership intensity in industry-school project-based learning - Yudi Wahyudi; Ana Ana; Isma Widiaty; Cica Yulia (Journal of Environment and Sustainability Education, 2026)
The assumption that more frequent industry involvement leads to higher-quality STEM-integrated learning has positioned industry–school collaboration as a key component of vocational education. This study critically examines this linear assumption by revealing a paradoxical empirical trend using a convergent mixed-methods approach, focusing on how vocational teachers broker STEM competency development across institutional boundaries. Quantitative results show that Project-Based Learning (PjBL) efficacy (M = 9.11, SD = 1.40; 82.7%) and partnership quality (M = 9.53, SD = 1.01) are both high. However, their relationship is weak and not statistically significant (r = 0.044, p = 0.918), indicating that stronger partnerships do not necessarily improve learning outcomes. Data were collected from 200 students and 40 stakeholders in eight public vocational high schools in Bandung, Indonesia. Qualitative data included 34 hours of observations, interviews with 24 key informants, and document analysis. Reflexive thematic analysis identified three partnership models: Minimal Direct Involvement, Periodic Evaluation, and Intensive Integrated, each capable of supporting effective PjBL and contextualized STEM learning. Vocational teachers act as pedagogical brokers by translating industry standards into learning objectives, scaffolding application, designing authentic STEM tasks, and facilitating meaning-making. These mechanisms can partially substitute direct industry involvement. Findings show that integrated STEM competency development depends more on pedagogical mediation quality than partnership intensity. Document analysis also reveals a gap between formal partnership agreements and their implementation in practice.